ANALISIS FAKTOR YANG MEMPENGARUHI KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELLITUSDI PUSKEMAS BLUTO SUMENEP - Mujib Hannan (Fakultas Ilmu Kesehatan, 2013)
Background: Diabetes mellitus results from insulin malfunction. Although, amount of excess glucose was used in the organs or tissues is very low. Medication adherence in patients with Diabetes Mellitus is important in achieving treatment goals and effective in preventing some of the complications of Diabetes Mellitus, so the importance of research on the analysis of factors affecting medication adherence in patients with Diabetes Mellitus in PHC Bluto Sumenep.Objective:To analyze thefactors affectingmedication adherencein patientswith Diabetes MellitusinPHCBlutoSumenep.Methods:The studywas a analiticcorrelationwithcross sectional approach. Data analyze by usingsimplelogistic regressionstatistical testwithαof 5%.Results: There were between factors influence the characteristics of the disease and its treatment to medication adherence in patients with Diabetes Mellitus in PHC Bluto Sumenep, There is no effect between intra-personal factors on medication adherence in patients with Diabetes Mellitus in Sumenep Bluto health center that included age, type of sex, educational level and marital status, There is the influence of interpersonal factors on medication adherence in patients with Diabetes Mellitus in health centers and Sumenep Bluto, There is the influence of environmental factors on medication adherence in patients with Diabetes Mellitus in PHC Bluto SumenepConclusions: Factorscharacteristicofthe diseaseandits treatmentandenvironmental factorsare dominant factorsaffectingmedication adherencein patientswith diabetesmellitusinPHCBlutoSumenep